Obstetric Knowledge, Attitude, and Behavior Concerning Periodontal Diseases and Treatment Needs in Pregnancy: Influencing Factors in France. Issue 3 (1st March 2015) - Cohen, Laura; Schaeffer, Mickaël; Davideau, Jean‐Luc; Tenenbaum, Henri; Huck, Olivier
Abstract : Background: Many studies have shown that periodontal diseases are risk factors for adverse pregnancy outcomes. The aim of this study is to assess the knowledge and clinical attitude of French obstetricians and/or gynecologists regarding periodontal diseases. Methods: A cross‐sectional study was performed on randomly selected French obstetricians and/or gynecologists using a self‐administered, structured questionnaire during an annual French professional congress. Results: The questionnaire was completed by 190 French obstetricians and/or gynecologists. Among respondents, 88% were aware of the inflammatory and infectious nature of periodontal diseases. Furthermore, 74.7% of respondents were conscious of its negative impact on pregnancy outcomes. Few obstetricians and/or gynecologists (26.3%) interviewed patients about oral health. Information on oral health was systematically provided to patients by 10.5% of the practitioners. However, 55.6% addressed this issue if they considered the patient at risk for pregnancy. Only 33.2% of practitioners systematically referred the patient to a dentist. Periodontal disease knowledge and consideration levels increased in more experienced practitioners with a private practice and a personal history of periodontal disease. Conclusions: Periodontal knowledge of the French obstetricians and/or gynecologists surveyed seemed satisfyingly apparent and influenced by levels of professional experience and personal history. However, clinical behavior did not adequately correlate with this knowledge.